nab-Paclitaxel/Carboplatin in Vulnerable Populations With Advanced Non-Small Cell Lung Cancer: Pooled Analysis - Langer, Corey J.; Gajra, Ajeet; Gridelli, Cesare; Konduri, Kartik; Morgensztern, Daniel; Spigel, David; Talbot, Denis; Thomas, Michael; Weiss, Jared; Pilot, Richard; Bhore, Rafia; Wolfsteiner, Marianne; et al. (Frontiers in Oncology, 2021)
Introduction: Despite improvements in the treatment of advanced non-small cell lung cancer (NSCLC), certain patient populations remain underrepresented in clinical trials. Many patients have benefited from platinum doublets, including nab-paclitaxel–based regimens, but there are patients with comorbidities who particularly require careful balancing of efficacy and safety. Clinical trial data are limited for patients who are elderly or have renal impairment, diabetes, or impaired performance status. Methods: To better understand outcomes in these patient populations, we performed a pooled analysis using data from the ABOUND clinical trial program (ABOUND.SQM, ABOUND.PS2, ABOUND.70+) and the key phase III trial of nab-paclitaxel/carboplatin in advanced NSCLC. The populations included in this pooled analysis consisted of elderly patients (≥ 70 years) and patients with renal impairment (eGFR < 60 mL/min/1.73 m2), diabetes, or poor performance status (ECOG PS 2). Results: Median progression-free survival (PFS) ranged from 4.1 months in patients with ECOG PS 2 (95% CI, 2.04-5.09 months) to 7.7 months in patients with diabetes (95% CI, 5.88-10.12 months). PFS for elderly patients and patients with renal impairment was 6.9 months each (95% CI, 6.01-7.98 months and 4.47-9.79 months, respectively). Median overall survival (OS) was 18.2 months (95% CI, 10.94-28.22 months), 17.4 months (95% CI, 14.59-20.14 months), and 16.1 months (95% CI, 14.09-18.50 months) in patients with renal impairment, patients with diabetes, and elderly patients, respectively. Patients with ECOG PS 2 exhibited the shortest median OS: 5.6 months (95% CI, 3.98-11.37 months). Overall response rates were 56.9%, 54.6%, 45.9%, and 29.4% in patients with diabetes, elderly patients, patients with renal impairment, and patients with ECOG PS 2, respectively. Most treatment-related adverse events were hematologic. The most common grade 3/4 hematologic adverse events in patients with renal impairment, elderly patients, patients with diabetes, and patients with poor performance status included neutropenia, anemia, and thrombocytopenia. Conclusions: Although survival data in patients with ECOG PS 2 were notably inferior to the other cohorts, our findings are consistent with those previously reported in the population-specific studies of the ABOUND trials and lend additional support for the use of nab-paclitaxel–based regimens in historically understudied and vulnerable populations.